Sexual desire and sexual arousal in Malaysian women: are they of the same entity? - Nik Jaafar, Nik Ruzyanei; Midin, Marhani; Wan Puteh, Sharifah Ezat; Musa, Ramli; Sidi, Hatta (ASEAN Federation of Psychiatry, 2009)
Objective: To investigate the correlation between sexual desire and sexual arousal among Malaysian women in a primary care setting. Methods: The Malay Version of Female Sexual Function Index (MVFSI) was used to assess low sexual desire and lack of sexual arousal among the respondents. A total of 230 married women aged 18 – 70 years old participated in this study. Their sociodemographic, marital profiles and correlation between low sexual desire and lack of sexual arousal were examined. Results: More than 60% respondents with low sexual desire have co-exist low sexual arousal and 94.4% respondents with high sexual desire do have high sexual arousal ( χ²= 79.6, p <0.001 ), with correlation of r = 0.852. Conclusions: The strong correlation between sexual desire and arousal has both diagnostic and therapeutic indications, and may also strongly support the circular model (Basson-inspired model) of sexual response among women.